PENGARUH SQUARE STEPPING EXERCISE DAN ANKLE STRATEGY EXERCISE TERHADAP KESEIMBANGAN PADA LANSIA - Sabri, Aiman; Sulaiman, Sulaiman; Maryaningsih, Maryaningsih (PHYSIO MOVE JOURNAL, 2023)
The health status of the elderly which declines with age will affect the quality of life of the elderly. Increasing age will be accompanied by the emergence of various diseases, decreased body function, body balance and the risk of falling. Research objectives: To analyze whether there is an effect of giving Square Stepping Exercise and Ankle Strategy Exercise to changes in the level of dynamic balance of the elderly. Research method: The design of this study is Quasi Experimental using "one group pretest posttest" which aims to determine the effect of Ankle strategy and Square Stepping Exercise in improving the dynamic balance of the elderly. Respondents given treatment in this study were Square Stepping Exercise and Ankle Strategy Exercise. Results: processed using SPSS with the normality test of the Shapiro Wilk test to determine the distribution of the data. Next, hypothesis testing was carried out. The subjects were women with 20 people with a percentage of 66.7% and 10 men with a percentage of 33.3%. initial treatment by getting a mean value of 65.70. the final condition of the subject obtained a mean value of 13.27. probability p0.05 was normal and statistical analysis was used parametric. the shapiro-wilk test results from the pre test, namely p0.117 and post-test p0.386. Conclusion: Paired Sample T-test The result is p0.001. Based on the research conducted, it is concluded that the exercise strategy and square stepping can improve balance in the elderly.